2018
DOI: 10.1016/j.bbrep.2018.07.005
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of antibody affinity by introduction of basic amino acid residues into the framework region

Abstract: Antibodies are widely used not only as therapeutic agents but also as research tools and diagnostic agents, and extensive efforts have been made to generate antibodies that have higher affinity. It was recently reported that introduction of charged residues into the framework region of an antibody improved its affinity; however, the underlying molecular mechanism has not been elucidated. In this study, we used kinetic and thermodynamic analyses of the antibody–antigen interaction to investigate the molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…For such antigens, one solution is to append epitope tags, such as FLAG, S, and V5 tags. Antibody engineering might also be used to produce fast-dissociating antibodies, for example, through amino acid substitutions within the antigen recognition sites of antibodies to accelerate dissociation from epitopes ( Fukunaga et al, 2018 ; Hugo et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…For such antigens, one solution is to append epitope tags, such as FLAG, S, and V5 tags. Antibody engineering might also be used to produce fast-dissociating antibodies, for example, through amino acid substitutions within the antigen recognition sites of antibodies to accelerate dissociation from epitopes ( Fukunaga et al, 2018 ; Hugo et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some antibodies in schizophrenia acquire catalytic activity and rather high rates of catalysis due to their lower affinity than those of tight binding autoantibodies. Binding affinity is determined by the number of bonds formed with the antigen, and accordingly is determined by the amino acid residues that form the CDR [ 60 ]. Therefore, it can be assumed that the antibodies of patients with catalytic activity have a specific CDR structure.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of an antibody-antigen binding, it is able to strengthen the connection through hydrogen bonds or electrostatic forces [66,67]. In 2018, Fukunaga et al showed that the introduction of lysine to the Fab region of an antibody improves its affinity to the given antigen [68]. In turn, Thommesen et al pointed out the key role of lysine in the human IgG3 for the complement activation [69].…”
Section: Discussionmentioning
confidence: 99%